A Korean Peninsula Free of Nuclear Weapons Perspectives on Socioeconomic Development - Bang, Chan Young (Cham : Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2023)
This book focuses on three main subjects: the DPRK's inability to survive as a nuclear state; the importance of China's role in encouraging denuclearization of the Korean Peninsula; and the possibility of an alternative political organization for the DPRK including a transition to a market-economy in exchange for giving up its nuclear weapons. The book approaches North Korean issues from the perspective that the regime cannot survive without nuclear weapons which, rather than being a genuine danger to other states, are bargaining chips for security and survival. The book includes views from prominent academics and practitioners, including a former British ambassador to North Korea, putting forward an ambitious set of recommendations and analyses based on hands-on experience in the region. Chan Young Bang, PhD, is president of KIMEP University in Almaty, Kazakhstan, Principal Investigator of its DPRK Strategic Research Center, and a former economic adviser to Nursultan Nazarbayev, first president of Kazakhstan. He has published numerous articles and books on the prospects for a peaceful settlement of the North Korean nuclear conflict.
1. Introduction -- 2. North Korea and the Nuclear Non-Proliferation Treaty. By Chan Young Bang -- 3. Only one approach to denuclearization will work, and it will bring economic benefits to South Korea. By Chan Young Bang -- 4. North Korea's nuclear capability and what the implications are for wider East Asia. By Sung-wook Nam -- 5. Learning to Love the Bomb: Depictions of Nuclear and Missile Technology in North Korean Literature. By Meredith Shaw -- 6. The North Korean Nuclear Issue: Root Causes and Solutions. By Zhibo Zou -- 7. The situation on the Peninsula out of the vicious circle requires consideration of the concerns of all sides. By Guohong Qiu -- 8. Can the DPRK Preserve Its Sovereignty Without Nuclear Armaments?. By John Everard -- 9. Armistice, North Korean nuclear crisis and peace regime on the Korean Peninsula. By Lei Wang.
Keywords: Security, International; International Security Studies